A Critical Review of the Pharmacokinetics, Pharmacodynamics, and Safety Data of Antibiotics in Avian Species - Hui Yun Soh; Prisca Xin Yi Tan; Tao Tao Magdeline Ng; Hui Ting Chng; Shangzhe Xie (MDPI AG, 2022)
In avian medicine, the use of antibiotic dosing regimens based on species-specific pharmacological studies is ideal. However, due to a lack of such studies, dose extrapolation, which may cause inefficacy and toxicity, is common practice. Multiple searches were performed using the PubMed and Web of Science databases to extract relevant pharmacological studies performed in exotic avian species. The pharmacokinetics (PK), pharmacodynamics (PD), and safety data of the selected antibiotics (enrofloxacin, marbofloxacin, gentamicin, amikacin, ceftiofur, doxycycline, and amoxicillin/clavulanate) from these studies were reviewed. This review aimed to identify trends amenable for safe inter-species dose extrapolation and provide updated findings on dosing regimens that are safe and efficacious for various exotic avian species. We observed that the half-life of antibiotics appears to be shorter in the common ostrich and that amikacin may be amenable to inter-species dose extrapolation as it is safe and shows little inter-species PK and PD variation. Species-specific enrofloxacin dosing regimens that were not listed in the Exotic Animal Formulary (5th ed.) were found for Caribbean flamingos, African penguins, southern crested caracaras, common ostriches, and greater rheas. Specific dosing regimens recommended for psittacine birds (doxycycline 130 mg/kg medicated water) and ratites (PO doxycycline 2-3.5 mg/kg q12 h, PO enrofloxacin 1.5-2.5 mg/kg q12 h and IM enrofloxacin 5 mg/kg q12 h) in the formulary may not be effective in budgerigars and common ostriches, respectively. Apart from the lack of species-specific pharmacological studies, a lack of multiple dose studies was also noted.